2019
DOI: 10.1109/access.2019.2926515
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis on Artificial Profiles and Electroencephalography Signals by Roughness Scaling Extraction Algorithm

Abstract: Electroencephalography (EEG) was widely investigated in brain status detection and disease diagnosis, in which the fractal analysis played an important role. In this paper, the roughness scaling extraction (RSE) algorithm proposed in our previous study on surface morphologies was applied to calculate the fractal dimensions (FDs) of artificial profiles and EEG signals. Fractal profiles with ideal FDs ranging from 1.01 to 1.99 were generated through the Weierstrass-Mandelbrot function. The RSE algorithm and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The denoising process for EEG signals was essential and there were lots of noise reduction methods, such as wavelet decomposition [28,29] and empirical mode decomposition (EMD) [30,31]. To be consistent with previous research, the denoising process in this study was wavelet decomposition with passband filtering and had been widely used to alleviate the noise influences [22,23,28,29]. The reason for the abovementioned difference of D variations were analyzed and it was found that the denoising operation had an important influence on D variation trend.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The denoising process for EEG signals was essential and there were lots of noise reduction methods, such as wavelet decomposition [28,29] and empirical mode decomposition (EMD) [30,31]. To be consistent with previous research, the denoising process in this study was wavelet decomposition with passband filtering and had been widely used to alleviate the noise influences [22,23,28,29]. The reason for the abovementioned difference of D variations were analyzed and it was found that the denoising operation had an important influence on D variation trend.…”
Section: Introductionmentioning
confidence: 64%
“…An important basis for using the fractal algorithms to detect epileptic seizures was the D variation during seizure status compared with normal status. However, it was found that some publications reported that D in the seizure status had a downward trend [21,24,25], while other literature reported an upward trend of D variation [20,22,23,26,27], and such a significant divergence and its cause had not been studied in the available literature. Such a significant difference seriously undermined the feasibility and even the reliability of fractal algorithms in epileptic detection.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Box-counting dimension algorithm is a classical method to calculate fractal dimension [44]. The Hurst index H is an important parameter in box-counting dimension method.…”
Section: A Fd-ls-eemdmentioning
confidence: 99%
“…In addition, Wang et al (2019) introduced a new algorithm named 'roughness scaling extraction' (RSE) to evaluate FD based on a single morphological image. It was found that RSE algorithm was much more accurate than the traditional algorithms.…”
Section: Fractal Analysismentioning
confidence: 99%